Increasing leaf vein density by mutagenesis: laying the foundations for C4 rice - Feldman, Aryo B.; Murchie, Erik H.; Leung, Hei; Baraoidan, Marietta; Coe, Robert; Yu, Su-May; Lo, Shuen-Fang; Quick, William P. (Public Library of Science, 2014)
A high leaf vein density is both an essential feature of C4 photosynthesis and a foundation trait to C4 evolution, ensuring the optimal proportion and proximity of mesophyll and bundle sheath cells for permitting the rapid exchange of photosynthates. Two rice mutant populations, a deletion mutant library with a cv. IR64 background (12,470 lines) and a T-DNA insertion mutant library with a cv. Tainung 67 background (10,830 lines), were screened for increases in vein density. A high throughput method with handheld microscopes was developed and its accuracy was supported by more rigorous microscopy analysis. Eight lines with significantly increased leaf vein densities were identified to be used as genetic stock for the global C4 Rice Consortium. The candidate population was shown to include both shared and independent mutations and so more than one gene controlled the high vein density phenotype. The high vein density trait was found to be linked to a narrow leaf width trait but the linkage was incomplete. The more genetically robust narrow leaf width trait was proposed to be used as a reliable phenotypic marker for finding high vein density variants in rice in future screens.